Study on the Relationship Between Confucian Filial Piety Culture and Chinese Youth’s Entrepreneurial Intention - Lily, Zhao; Fanzhu, Kong; Xiurang, Yang (Frontiers in Psychology, 2022)
As an important part of entrepreneurial environment, Culture directly or indirectly affects individual entrepreneurial intention. Taking young students as the survey object, this paper uses empirical research methods to explore the relationship between Confucian filial piety culture and Chinese youth's entrepreneurial intention. The results show that there is a positive correlation between Confucian filial piety culture and Chinese youth's entrepreneurial intention, achievement motivation, risk-taking tendency and self-efficacy; Confucian filial piety culture has not only a direct effect on Chinese youth’s entrepreneurial intention, but also an indirect effect with achievement motivation, self-efficacy and risk-taking tendency as intermediary variables.